Breastfeeding in the midst of adversity: an interpretative phenomenological analysis of breastfeeding in adolescent mothers - Atefeh Yas; Fatemeh Zahra Karimi; Abbas Heydari; Javad Moghri; Talat Khadivzadeh (BMC Public Health)
Abstract Background Breastfeeding prevalence, exclusive breastfeeding, and continuous breastfeeding until two years of age are less common among adolescent mothers than in adult mothers. Using a phenomenological approach, the present study aimed to explore the lived experiences of breastfeeding among adolescent mothers. Methods The present qualitative study was written using Van Manen's descriptive-interpretive phenomenology approach. Purposive sampling was conducted to achieve maximum variation. Data were gathered through a semi-structured face-to-face interview with 10 primiparous adolescent mothers. The interviews continued until the data were saturated. The data were analyzed using 3 th - 6 th stages of Van Manen's approach with MAXQDA software (version10). Results Four main themes were identified concerning the breastfeeding experience of primiparous adolescent mothers: (1) challenges and obstacles of breastfeeding in adolescent mothers, (2) attitudes and social support with successful breastfeeding, (3) experience significant changes in life after breastfeeding, and (4) the paradox of adolescent mothers'feelings about breastfeeding. These four main themes were formed by combining the eleven subthemes. Adolescent mothers face numerous challenges during breastfeeding, including: breast issues like nipple soreness, premature infants and their inability to suck effectively, insufficient breastfeeding skills in the mother, prolonged hospitalization of the baby in the intensive care unit, pressure from those around to use formula, lack of social support from family and healthcare providers, societal judgment, poverty and life difficulties, and feelings of failure after discontinuing exclusive breastfeeding. Conclusions The current study revealed that adolescent mothers face various challenges during breastfeeding, and these mothers require considerable social support from their families, policymakers, and healthcare providers to succeed in this endeavor. Additionally, breastfeeding offers mothers a sense of maternal identity, and the success or failure of breastfeeding significantly impacts their emotional well-being. Therefore, it is recommended that families and healthcare providers develop necessary interventions to educate and support these mothers in their breastfeeding journey.